Comparison of milk production and composition of saanen and shami - jamnapari crossbred goats - Sairuddin, Solehah (2017)
The self-sufficiency level for milk goat in Malaysia is very low, only 12.93% in 2014. Despite that, some farmers in Malaysia are crossing the Shami goat with Jamnapari as well as Saanen producing Shami crossbreds to serve as milk producers. There is a need to evaluate the milk production and quality of Shami goats and their crosses in Malaysia. There are very limited published studies on the milk quality of the Shami goats, and none of those in Malaysia. This study was conducted to evaluate the milk quality and production of Saanen and Shami-Jamnapari crossbreds. The specific objectives of this study were to evaluate the milk composition and production of purebred Saanen and crossbred Shami goats at different stages of lactation to examine the differences in the milk composition of the two breed types and to determine the association between the various milk quality traits investigated in the breed types. Two breed types of dairy goats at a dairy goat farm in Batang Benar, Nilai were used, namely the purebred Saanen goat and the Shami-Jamnapari crossbred. Twenty lactating goats were used (10 Saanen goats and 10 Shami-Jamnapari crossbred). These does was randomly selected from the lactating animals at the farm. The age of the does were between 1-5 years. The does were in early to late lactation. The experimental design that was used is completely randomized design. Milk samples were collected twice daily (morning at 6 a.m. and evening at 4 p.m) on alternate weeks over two months. Milk samples (20 ml) were collected from the lactating goats. The milk collected at each milking was weighed and recorded. Samples (20 ml) of the milk collected in the morning were transferred to the laboratory in ice for analysis of the milk composition. The date of kidding for each doe were recorded to determine days in milk. The milk samples were stored at 4oC for 24 hours before being analysed for milk components using the MilkoScanTM, an infrared based milk analyser. All the milk samples were analysed in triplicates and the average of the results were recorded. Effect on breed by lactation number interaction showed no significant (P>0.05) difference for milk yield at all four collections. Breed showed a significant (P<0.05) effect on milk yield only at the first collection. There were no significant (P>0.05) differences between the breeds for second to fourth collection. Lactation number showed no significant (P>0.05) effect on milk yield for the four collections. Breed by lactation number interaction effect was not significant (P>0.05) for all milk composition traits. Breed showed a significant (P<0.05) effect on fat A, fat B, protein, lactose, total solid and solid-non-fat. There was no significant (P>0.05) effect of lactation number on fat A, fat B, protein, total solid and solid-non-fat, but lactation number showed a significant (P<0.05) effect on the lactose content.